KEHARUSAN MEMBERI LANDASAN TRANSENDENTAL DALAM MENGELOLA PENDIDIKAN - Irwan Saleh Dalimunthe (Jurnal Al-Fatih, 2019)
Surah al-‘Alaq is a guidance suggested by Allah to guide people life in this world and eternal life hereafter. Morality massage of this verse is to manage life by tawhid basic. Tawhid or faith to Allah has a fundamental and strategic value in life journey of a moslem as a personal and also in a comunal in a civilization. But this verse signs that faith can not be emerge without a knowledge (understanding the nature as a creation of Allah). So, in this context, knowledge becomes as a significant to create the truth faith. Knowledge is a tool to understand Allah and makes people can understand the truth of Allah. So, the nature is a medium to understand Allah correctly and to study it is a must by ‘ainul yakin approach. The problem is that education paradigm in epistemologi and aksiologi positioned simply and tends pragmatically by securalism and materialism basic. It makes a civilization prinsiple emerge without humanity appreciation. So that, education Tawhid (unity of one God) must be reseach and master knowledge (science-nature) as a part to streghten the faith, function and duty of life. If it is not, the knowledge will not make the goodness for people but keeping away from Allah and earth will not become the good place for resident.